Pengaruh Angkatan Kerja dan Investasi Terhadap Aglomerasi Industri di Pulau Sumatera Dalam Perspektif Ekonomi Islam (Analisis Data Panel 2018-2024) - Veri Yulianto; Dimas Pratomo; Citra Etika (Jurnal Ilmiah Ekonomi Islam, 2026)
This study analyzes the influence of labor force and investment on industrial agglomeration in Sumatera Island from an Islamic economics perspective during 2018–2024. The study employs a quantitative approach using panel data covering 10 provinces in Sumatera Island. The study obtained secondary data from Statistics Indonesia (BPS) and analyzed them using panel data regression techniques. Model selection used the Chow and Hausman Tests, which indicated that the Fixed Effect Model (FEM) was the most appropriate estimation model. The results show that the labor force variable has a positive and significant effect on industrial agglomeration, with a coefficient of 0.219315 and a probability value of 0.0492. Meanwhile, investment has a negative and insignificant effect on industrial agglomeration, with a coefficient of -0.003042 and a probability of 0.8274. Simultaneously, labor force and investment significantly affect industrial agglomeration, as indicated by an F-statistic probability value of 0.000000. The Adjusted R-squared value of 0.994003 indicates that labor force and investment explain 99.40% of the variation in industrial agglomeration, while the remaining 0.60% is explained by factors outside the model. From the perspective of Islamic economics, labor force and investment are strategic instruments for promoting economic development that is just, balanced, and oriented toward public welfare (maslahah). Therefore, industrial agglomeration should be directed not only to improve economic efficiency but also to achieve equitable regional development in accordance with the principles of al-'adl (justice), tawazun (balance), and maslahah (public interest).